The Influence of Qiraat Knowledge on Arabic Grammar - Wirdah Fachiroh (Interdisciplinary Social Studies, 2025)
The science of Qiraat constitutes a foundational source for Arabic grammatical study (Nahwu). Addressing scholarly polemics regarding variances in Qiraat and its application as qiyas (analogical reasoning) within Arabic grammatical methodology, this research aims to: introduce Qiraat knowledge through its definition, conditions, and historical development; and elucidate its functional benefits for Arabic grammatical methodologies, supplemented by examples. Employing a descriptive-analytical methodology, the researcher presents a surah to demonstrate variant recitations. Through analytical examination, selected Qiraat samples are evaluated as paradigmatic models for methodological application. The study concludes that Qiraat variations originate in narrations from the Prophet's companions (PBUH), subsequently disseminated across Arabian regions including Madinah, Sham, and Basra. These divergent transmissions significantly contributed to the expansion and refinement of Arabic grammatical systems—specifically the science of Nahwu.